Popularity of digital hadith application (DHA) in Malaysia - Halim A.A.; Anas N.; Zulkipli S.N.; Yaacob Z.; Mohd Noor M.S.; Mohd Ghazali Z.; Azmi A.S.; Hassan S.N.S. (IAEME Publication, 2024)
Indexed by SCOPUS